2018
DOI: 10.3390/agronomy9010003
|View full text |Cite
|
Sign up to set email alerts
|

Maize Canopy Photosynthetic Efficiency, Plant Growth, and Yield Responses to Tillage Depth

Abstract: Subsoil tillage loosens compacted soil for better plant growth, but promotes water loss, which is a concern in areas that are commonly irrigated. Therefore, our objective was to determine the physiological responses of high yield spring maize (Zea mays L.) to subsoil tillage depth when grown in the Western plain irrigation area of Inner Mongolia, China. Our experiment during 2014 and 2015 used Zhengdan958 (Hybrid of Zheng58 × Chang7-2, produced by Henan academy of agricultural sciences of China, with the chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
5
17
0
Order By: Relevance
“…Grain yield increases in response to narrow rows has been found to be closely related to an improvement in PAR interception during the critical period for grain set (Andrade et al., 2002). These results suggest that the optimum LAI for corn to produce grain yield during maximum LAI is between 6 and 6.5, which is similar to previous studies evaluating LAI in corn (Sun et al., 2019; Winter & Ohlrogge, 1973).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Grain yield increases in response to narrow rows has been found to be closely related to an improvement in PAR interception during the critical period for grain set (Andrade et al., 2002). These results suggest that the optimum LAI for corn to produce grain yield during maximum LAI is between 6 and 6.5, which is similar to previous studies evaluating LAI in corn (Sun et al., 2019; Winter & Ohlrogge, 1973).…”
Section: Resultssupporting
confidence: 89%
“…Grain yield increases in response to narrow rows has been found to be closely related to an T A B L E 3 Canopy coverage at V5 and V8, R1 stem diameter, and R1 plant height as influenced by row spacing (76 and 51 cm) and plant population for corn averaged across six hybrids and two locations in 2017 and 2018 improvement in PAR interception during the critical period for grain set (Andrade et al, 2002). These results suggest that the optimum LAI for corn to produce grain yield during maximum LAI is between 6 and 6.5, which is similar to previous studies evaluating LAI in corn (Sun et al, 2019;Winter & Ohlrogge, 1973).…”
Section: Leaf and Plant Characteristicssupporting
confidence: 85%
“…The length of the error bars revealed that the concentration of values used in the analysis is high and thus the average value is certain. These results corroborate the findings of Hakansson and Lipiec (2000) and Sun et al (2018), where the researchers concluded that soil bulk density increases with compaction and decreases when the soil is pulverized. On the other hand, there is an inverse proportionality relationship between the soil moisture content and the level of soil compaction.…”
Section: Soil Bulk Density and Moisture Contentsupporting
confidence: 90%
“…The recipient maize cultivar was Zhengdan958 (Z958, Hybrid of Zheng58 × Chang7-2) and the EPSPS transgenic herbicide-tolerant maize line was CC2 (produced by the insertion of the maroACC gene) (Yan et al, 2018; Sun et al, 2019). The experimental fields were located in Yuanyang, Xinxiang City, Henan Province, China (N 35.011°, E 113.711°) and Zhangqiu, Jinan City, Shandong Province, China (N 36.780°, E 117.384°).…”
Section: Methodsmentioning
confidence: 99%